(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This article describes the phytosanitary state of apricot cultivation in the climatic conditions of Uzbekistan, the main factors negatively affecting productivity, and effective strategies for their control. The study examined the distribution dynamics of dangerous objects such as shot-hole (clasterosporium), moniliosis (fruit rot), and the apricot fruit moth. The possibilities of reducing crop loss through the harmonious use of modern chemical preparations and biological protection agents are analyzed.